Household clean energy consumption and health: Theoretical and empirical analysis - Li, Fanghua; Liang, Wei; Chandio, Abbas Ali; Zang, Dungang; Duan, Yinying (Frontiers in Public Health, 2022)
The impact of energy consumption on health has become a widely discussed topic worldwide. However, much of the current research on this topic lacks a theoretical basis. Hence, this paper adopts both theoretical analysis and empirical analysis to explore the impact of household clean energy consumption on residents' health. Firstly, based on the theory of health economics and energy economics, this paper believes that the use of clean energy can improve people’s health. Then, this study uses the data from the 2018 China Health and Retirement Longitudinal Study as the sample, and the Order Probit Model was used for the empirical analysis. The results of basic regression, robustness testing, and treatment of endogenous issues indicate that clean energy consumption has significantly improved the health level of residents. Further, the heterogeneity analysis showed that long-term use of clean energy significantly enhanced the health of non-religious people and had a more obvious effect on the health of women as well as poor residents. In addition, the mechanistic analysis exhibited that subjective happiness and air quality played a partial mediating role among the cleaner energy consumption impact on health. Finally, the incidence rates of hypertension, hyperlipidemia, lung disease, asthma, and depression were significantly reduced by cleaner household energy. The conclusions of this paper support the views of some existing literature, and five policy recommendations are put forward based on the research findings.